Comparative politics today : a world view - Almond, Gabriel A.;Powell, G. Bingham, Jr. (Glenview, Illinois : Scott, Foresman and Company, 1988)
In the fourth edition of comparative politics today: a world view we have maintained the successful theoretical framework and thematic balance of the previous edition, while updating and extending the country coverage.
Part One. Introduction -- Part Two. Systems, process, and policy -- Part Three. Country studies.
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE